PRE-SERVICE TEACHERS’ SELF-REGULATED LEARNING STRATEGY, MOTIVATION, AND REVISION BEHAVIORS IN EFL ACADEMIC WRITING - Nabhan, Salim (IKIP PGRI Pontianak, 2019)
The present study explored pre-service teachers? self-regulated learning strategyand motivation in EFL academic writing. A further aim of the study is toinvestigate the relationship between their self-regulated learning strategy andmotivation as well as to explore the revision behaviors in English academicwriting. A questionnaire was administered to 56 pre-service teachers (PST)majoring English language education. The questionnaire covered 16 items ofquestions regarding self-regulated learning strategy comprising environmentalprocess, behavioral process, and personal process, as well as motivation. PSTs?revisions of academic writing were also assessed using writing revision categoriesto identify their revision behaviors. Descriptive analyses indicated thatparticipants were moderate to high in their self-regulated learning strategy andmotivation toward their writing activities. Furthermore, the result showed thatdespite the fact that self-regulated learning strategy in the aspect of environmentalstrategy and personal strategy did not significantly correlate with motivation,behavioral strategy significantly correlated with motivation. In addition to this,among the revision categories, the aspects of organization, citation, mechanics,language use, and references were the most common categories of revisions,while content and format were the least ones. The study might have implicationon the PST?s EFL academic writing instruction.Keywords: self-regulated learning strategy, motivation, revision, EFL academicwriting